Application of Inquiry Learning Methods to Increasing Students' Interest in Speaking English - Yuna Mumpuni Rahayu (Equivalent: Jurnal Ilmiah Sosial Teknik, 2023)
This study investigates how the implementation of InquiryInquiry can improve students' interest in speaking English in class VII in Public Junior High School 18 Cirebon. This collaborative classroom action research did in two cycles, and the participants of this study participants were 24 students from the target class, consisting of 12 girls and 12 boys. The researcher herself acted as an observer, and one of the English teachers from the target school acted as a teacher (collaborator). This is a descriptive-qualitative study because this study investigates the value of teaching speaking. The findings from the classroom observation, the video recorded, and the field notes were analyzed and then described according to the relevant theorists. The findings proved that InquiryInquiry improved students' interest in learning speaking in class VII Public Junior High School 18 Cirebon. The improvement in the student's interest was proved by the student's enthusiasm and the students' joy during the teaching process. It also proved from the students' responses during discussion sessions and practising and from the students' exposure to using English during the lesson. Implementing InquiryInquiry in teaching English facilitates students to do maximal in doing their best during the learning process. However, InquiryInquiry consumes time and is unsuitable for many students in a classroom. Inquiry facilitates freedom for students in finding their knowledge through learning, but it only ensures students' focus on their studies if the teacher does maximal management and scaffolding. Thus, the findings above made the researcher suggest a more prominent study with sufficient time and broadened Cycle for better results.